Unlocking Sustainable Private Sector Growth in the Middle East and North Africa : Evidence from the Enterprise Survey - World Bank; European Bank for Reconstruction and Development; European Investment Bank (Luxembourg City: European Investment Bank; London: European Bank for Reconstruction and Development; Washington, DC: World Bank, 2022)
Economic growth in the Middle East and North Africa (MENA) has been weak since the global financial crisis of 2007-09 and the Arab Spring of the early 2010s. Achieving higher and sustainable growth is particularly important in view of other economic challenges facing the region: public debt in MENA countries has increased considerably over the last decade, accompanied by declining investment. This report seeks to understand what lies beneath that relatively slow growth, with a particular focus on the reasons for stagnating productivity and inadequate accumulation of human capital and physical capital in the region’s private sector. To this end, the report summarizes the main findings from nine background papers based on enterprise survey data. It also draws conclusions for policy, not only for promoting stronger firm performance, but also for addressing the challenge of climate change by pursuing sustainable growth.